Beispiel Nr: 22
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ -7x +9y =-3\\ 5x -6y = -4 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad -7 x +9 y =-3\\ II \qquad 5 x -6 y = -4 \\ \text{I nach x auflösen}\\ -7 x +9 y =-3 \\ -7 x +9 y =-3 \qquad /-9 y\\ -7 x =-3 -9 y \qquad /:\left(-7\right) \\ x =\frac{3}{7} +1\frac{2}{7} y \\ \text{I in II}\\ 5 (\frac{3}{7} +1\frac{2}{7} y ) + -6 y = -4 \\ 2\frac{1}{7} +6\frac{3}{7} y -6 y = -4 \qquad / -2\frac{1}{7} \\ +6\frac{3}{7} y -6 y = -4 -2\frac{1}{7} \\ \frac{3}{7} y = -6\frac{1}{7} \qquad /:\frac{3}{7} \\ y = \frac{-6\frac{1}{7}}{\frac{3}{7}} \\ y=-14\frac{1}{3} \\ x =\frac{3}{7} +1\frac{2}{7} y \\ x =\frac{3}{7} +1\frac{2}{7} \cdot \left(-14\frac{1}{3}\right) \\ x=-18 \\ L=\{-18/-14\frac{1}{3}\} \end{array} & \begin{array}{l} I \qquad -7 x +9 y =-3\\ II \qquad 5 x -6 y = -4 \\ \text{I nach y auflösen}\\ -7 x +9 y =-3 \\ -7 x +9 y =-3 \qquad /+7 x\\ 9 y =-3 +7x \qquad /:9 \\ y =-\frac{1}{3} +\frac{7}{9}x \\ \text{I in II}\\ 5x + -6(-\frac{1}{3} +\frac{7}{9} x ) = -4 \\ 2 -4\frac{2}{3} x -6 x = -4 \qquad / -2 \\ -4\frac{2}{3} x -6 x = -4 -2 \\ \frac{1}{3} x = -6 \qquad /:\frac{1}{3} \\ x = \frac{-6}{\frac{1}{3}} \\ x=-18 \\ y =-\frac{1}{3} +\frac{7}{9} x \\ y =-\frac{1}{3} +\frac{7}{9} \cdot \left(-18\right) \\ y=-14\frac{1}{3} \\ L=\{-18/-14\frac{1}{3}\} \end{array} \end{array} $